Proyecto de regeneración barrial en el Sector Carit, Cristo Rey - Santos-Guardia, Christian (Instituto Tecnológico de Costa Rica., 2019)
Neighborhood improvement and neighborhood regeneration are the lines in which the project is located. The research is based on conducting a study for two very important neighborhoods in San José, Costa Rica, specifically in the district Hospital, called “Barrio Carit” and “Barrio Cristo Rey”. These neighborhoods are part of what are known as “barrios del sur” with an important history and mostly residential buildings bisides a mostly working population. The project tries to understand the operation and weaknesses of the neighborhoods, and how to improve it with an urban intervention and the proposal of some architectural projects. It also seeks to respond to the needs of its population and have a close participation with the community, visit it, analyze it and even make it part of the project, in a way that they makes it their own. Finally, the project consists in an urban and architectural proposal, improving the collective equipment of the area, the urban space and proposing a portfolio of projects necessary to complete the proposal.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Costa Rica, San José; Vivienda social; Rehabilitación urbana; Espacio urbano; Urbanismo – Regeneración; Arquitectura